Lighthouse horrors : tales of adventure, suspense, and the supernatural - Waugh, Charles G.; Waugh, Charles; Greenberg, Martin Harry; Azarian, Jenny-Lynn. (Camden, Me. : Down East Books, 1993)
Storm-swept, remote light stations$1 (Band the isolated souls who man the beacons$1 (Bare the perfect inspirations for tales of suspense and horror. Lighthouse Horrors collects 17 of the best from such writers as Rudyard Kipling, Robert Bloch, Jack Vance, and Ray Bradbury.s
The disturber of traffic / Rudyard Kipling -- The lighthouse keeper's secret / Anonymous -- The end of the reef / T. Jenkins Hains -- Ghost Island light / John Fleming Wilson -- The woman at Seven Brothers / Wilbur Daniel Steele -- On the Isle of Blue Men / Robert W. Sneddon -- Madhouse light / Charles Francis Coe -- Three skeleton key / George G. Toudouze -- The fog horn / Ray Bradbury -- The light-house / Robert Bloch & Edgar Allan Poe -- When the five moons rise / Jack Vance -- All the way home / Dan J. Marlowe -- The door below / Hugh B. Cave -- By the hair of the head / Joe R. Lansdale -- Land's end / Delia Sherman -- The driven snow / Edward Wellen.
Keywords: Horror tales, American; Lighthouses -- Fiction